Fundamental factors of firm value: Evidence from the cement industry in Indonesia - Widyarti Kusumowardhani (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2020)
This study aims to analyze the factors which influence firm value. This study uses multiple regression analysis and takes data from three cement companies listed on the IDX. The results of this study concluded that companies must be efficient and keep the debt ratio to maintain the firm value.